Clinical azole cross-resistance in Candida parapsilosis is related to a novel MRR1 gain-of-function mutation. (December 2022) - Branco, Joana; Ryan, Adam P.; Pinto e Silva, Ana; Butler, Geraldine; Miranda, Isabel M.; Rodrigues, Acácio G.
Abstract: Objectives: Hereby, we describe the molecular mechanisms underlying the acquisition of azole resistance by a Candida parapsilosis isolate following fluconazole treatment due to candiduria. Methods: A set of three consecutive C. parapsilosis isolates were recovered from the urine samples of a patient with candiduria. Whole-genome sequencing and antifungal susceptibility assays were performed. The expression of MRR1, MDR1, ERG11 and CDR1B (CPAR2_304370) was quantified by RT-qPCR. Results: The initial isolate CPS-A was susceptible to all three azoles tested (fluconazole, voriconazole and posaconazole); isolate CPS-B, collected after the second cycle of treatment, exhibited a susceptible-dose–dependent phenotype to fluconazole and isolate CPS-C, recovered after the third cycle, exhibited a cross-resistance profile to fluconazole and voriconazole. Whole-genome sequencing revealed a putative resistance mechanism in isolate CPS-C, associated with a G1810A nucleotide substitution, leading to a G604R change in the Mrr1p transcription factor. Introducing this mutation into the susceptible CPS-A isolate ( MRR1 RI ) resulted in resistance to fluconazole and voriconazole, as well as up-regulation of MRR1 and MDR1 . Interestingly, the susceptible-dose–dependent phenotype exhibited by isolate CPS-B was associated with an increased copy number of the CDR1B gene. The expression of CDR1B was increased in both isolates CPS-B and CPS-C and in the MRR1 RI strain, harbouring the gain-of-function mutation. Conclusions: Our results describe clinical azole cross-resistance acquisition in C. parapsilosis due to a G1810A (G604R) gain-of-function mutation, resulting in MRR1 hyperactivation and consequently, MDR1 efflux pump overexpression. We also associated amplification of the CDR1B gene with decreased fluconazole susceptibility and showed that it is a putative target of the MRR1 gain-of-function mutation.